Evaluation of the grating period based on laser diffraction by using a mode-locked femtosecond laser beam - Yuki SHIMIZU; Kentaro UEHARA; Hiraku MATSUKUMA; Wei GAO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2018)
This paper presents a newly proposed method referred to as the femtosecond laser diffraction method for measurement of the grating period. The proposed method is established in such a way that a mode-locked femtosecond laser beam is employed as a light source for the traditional laser diffraction method, in which the Littrow configuration is utilized to evaluate grating period. Since the optical modes in a mode-locked laser, which are often referred to as the optical frequency comb, have deterministic mode frequencies with equal intervals in frequency domain, multiple diffracted beams in the same diffraction order can be obtained. By utilizing the number of Littrow angles obtained from the multiple diffracted beams in the same diffraction order, highly accurate measurement of the grating period can be expected. In this paper, as the first step of research, a prototype optical setup with a mode-locked femtosecond laser source is developed, and some basic experiments are carried out to demonstrate the feasibility of proposed method.